Human sex reversal is caused by duplication or deletion of core enhancers upstream of SOX9 - Brittany Croft (Nature Portfolio, 2018)
SRY and its target SOX9 are known key determinants in testis development. Here the authors by studying duplications and deletions upstream of SOX9 from patient samples with disorders of sex development (DSD) reveal enhancers for SOX9 critical for human sex development and DSD.